2015
DOI: 10.1021/acsami.5b09797
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Study To Suppress Charge Carrier Recombination for High Efficiency Perovskite Solar Cells

Abstract: We report effects of an interface between TiO2-perovskite and grain-grain boundaries of perovskite films prepared by single step and sequential deposited technique using different annealing times at optimum temperature. Nanoscale kelvin probe force microscopy (KPFM) measurement shows that charge transport in a perovskite solar cell critically depends upon the annealing conditions. The KPFM results of single step and sequential deposited films show that the increase in potential barrier suppresses the back-reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 34 publications
5
84
0
Order By: Relevance
“…The photocurrent distribution maps of CH 3 NH 3 SnI 3 is in agreement with the current distribution of lead-based perovskites. 22,23 It was earlier observed that the higher short-circuit current appears near GBs of CH 3 NH 3 PbI 3 rather than within grain interior. 22 Comparatively low local current was measured in the vicinity of GB 2 where there was a dip in the film morphology.…”
Section: -9mentioning
confidence: 97%
See 1 more Smart Citation
“…The photocurrent distribution maps of CH 3 NH 3 SnI 3 is in agreement with the current distribution of lead-based perovskites. 22,23 It was earlier observed that the higher short-circuit current appears near GBs of CH 3 NH 3 PbI 3 rather than within grain interior. 22 Comparatively low local current was measured in the vicinity of GB 2 where there was a dip in the film morphology.…”
Section: -9mentioning
confidence: 97%
“…Based on CS-AFM analysis and local current mapping, it was noticed that the photocurrent is most prominent around grain boundaries for both samples which is in agreement with photocurrent distribution for lead based perovskites. 23 The increase in carrier mobility in DMF based sample may be attributed to the higher crystallinity of the film, allowing an efficient pathway for charge transport, thereby improving charge collection.…”
Section: -12mentioning
confidence: 99%
“…The morphologies of the films annealed at different temperatures for 5 min were shown in Figure 2a. [24][25][26] Though the crystalline of the films can be further improved as the film is selenized at 340-380 °C, the quality of PN junction is gradually destroyed. Subsequently, when the selenization temperature increases to 300 °C, the small grains gradually fuse together with emerging boundaries.…”
Section: Growth Of Bandgap Gradient Sb 2 (Sse) 3 Filmmentioning
confidence: 99%
“…The CuI layer on a spin-coated TiO 2 compact layer might not allow extraction of electrons from perovskite to TiO 2 due to the higher conduction-band energy level (≈−2.2 eV) [26] than that of perovskite (≈−3.93 eV). [28] Therefore, if the surface of the spin-coated TiO 2 compact layer is only partially coated by CuI, the p-type character of CuI consisting of small-sized Cu + and large-sized I − (e.g., Li-TFSI) could act as PbI 2 (Pb 2+ + 2I − ) and Li + cation at the interface between TiO 2 ETL and perovskites as mentioned above, [27,28] simultaneously. [28] Therefore, if the surface of the spin-coated TiO 2 compact layer is only partially coated by CuI, the p-type character of CuI consisting of small-sized Cu + and large-sized I − (e.g., Li-TFSI) could act as PbI 2 (Pb 2+ + 2I − ) and Li + cation at the interface between TiO 2 ETL and perovskites as mentioned above, [27,28] simultaneously.…”
mentioning
confidence: 99%